NMDA receptor antagonist induced c-Fos expression in the medial entorhinal cortex during postnatal development - Liang, Feng; Wang, Hong; Naumann, Robert Konrad (Frontiers in Neural Circuits, 2025)
N-methyl-D-aspartate receptor (NMDAR) antagonists, including ketamine, phencyclidine (PCP), and dizocilpine (MK-801), are an important class of drugs that can produce antidepressant, hallucinogenic, dissociative, psychotomimetic, and anesthetic effects in humans and animal models. To understand the effects of NMDAR antagonists on the brain, it is essential to map their actions at cellular resolution. We quantified c-Fos expressing cells in the mouse telencephalon after systemic injection of the potent NMDAR antagonist MK-801 and found a 10-fold higher density of c-Fos in the medial entorhinal cortex (MEC) compared to other regions of the telencephalon. c-Fos density was high in layer 3 of the dorsal MEC but low in other parts of the MEC. Since previous studies have shown that parvalbumin (PV) staining shows a strong dorsal-ventral gradient in the MEC, we investigated the spatial correlation between c-Fos and PV staining. We classified PV neurons based on their level of immunoreactivity and found that high and medium PV neurons were positively correlated with c-Fos density, while low PV neurons were negatively correlated. To understand the temporal correlation of c-Fos and PV staining, we examined their expression patterns after MK-801 injections during postnatal development. PV expression emerged on postnatal day 12, preceding c-Fos expression, which emerged on postnatal day 16. Our results suggest that local circuits comprising specific subtypes of inhibitory and excitatory neurons are critical for generating a sustained neuronal response to NMDAR antagonists. Furthermore, a high density of PV neuron input may be a prerequisite for the induction of c-Fos expression observed in MEC principal neurons. This study contributes to our understanding of how the brain responds to NMDAR antagonists in the developing and adult brain and reveals cell types in the dorsal MEC that are highly sensitive to this class of drugs.